Penerapan Mesin 3D Print Dalam Pembuatan Rancangan Produk Perhiasan di PT. Kapit Mas - Yogi Artana, I Putu; Gede Arimbawa , I Made; Dana, I Nyoman (Pusat Penerbitan LPPM ISI Bali, 2024)
Jewelry is an object used to decorate body parts. The production process of making jewelry in the modern era currently utilizes sophisticated technology such as computer-aided design (CAD) and 3D printing machines. Today, many jewelry companies use (CAD) technology and 3D printing machines to facilitate the process of realizing jewelry, one of which is at PT. Kapit Mas. PT. Kapit Mas uses a 3D printer direct casting machine, namely a 3D printer machine that can be directly waxed with the Uniway brand. Another advantage of the Uniway machine is that this machine can print 3D with a high level of detail. The jewelry creation process at PT. Kapit Mas is carried out using the methods of observation, interviews, literature studies and active participation. The selection of this method is in line with the way the jewelry creation process is carried out at PT. Kapit Mas. The application of very modern technology, namely computer-aided design (CAD) and the Uniway 3D printing machine, makes it easier to make pendant, earrings, rings, charms and earcuff jewelry. In addition, other supporting tools and technologies also make it easier to make jewelry. PT. Kapit Mas uses CAD and 3D printing to simplify the process of jewelry realization, the application of 3D printing direct casting machines greatly facilitates the creation of jewelry samples where jewelry samples can be created in various sizes very quickly and with great precision